2022
DOI: 10.1038/s41420-022-01094-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-15a and miR-20b sensitize hepatocellular carcinoma cells to sorafenib through repressing CDC37L1 and consequent PPIA downregulation

Abstract: Sorafenib is a classical targeted drug for the treatment of advanced hepatocellular carcinoma (HCC), but intrinsic resistance severely limited its therapeutic effects. In the present study, we aimed to identify crucial genes in HCC cells that affect sorafenib resistance by a CRISPR/Cas9 genome-scale screening. The results indicated that the deficiency of miR-15a and miR-20b contributed to sorafenib resistance, whereas exogenous expression of miR-15a and miR-20b enhanced sorafenib sensitivity of HCC cells by ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The proteomic analysis found that PPIA may be a potential diagnostic marker for salivary gland tumors (de Lima‐Souza et al, 2022). In hepatocellular carcinoma, the binding between heat shock protein 90 (HSP90) and PPIA effectively increased the expression of PPIA, making cancer cells more resistant to sorafenib, reducing the efficacy of this targeted drug, and resulting in poor prognosis in patients (L. Li et al, 2022). PTPRS is a receptor‐type protein tyrosine phosphatase, which has been reported to modulate numerous signaling pathways (Bunin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The proteomic analysis found that PPIA may be a potential diagnostic marker for salivary gland tumors (de Lima‐Souza et al, 2022). In hepatocellular carcinoma, the binding between heat shock protein 90 (HSP90) and PPIA effectively increased the expression of PPIA, making cancer cells more resistant to sorafenib, reducing the efficacy of this targeted drug, and resulting in poor prognosis in patients (L. Li et al, 2022). PTPRS is a receptor‐type protein tyrosine phosphatase, which has been reported to modulate numerous signaling pathways (Bunin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical efficacy of Sorafenib treatment in HCC is modest, and it can only extend patients’ median overall survival by 3 months 30 . The existence of intrinsic or acquired drug resistance is considered a major obstacle contributing to the failure of sorafenib treatment in HCC patients 31,32 . Previous studies have shown that sorafenib treatment restrained tumor growth partly through suppression of tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 30 The existence of intrinsic or acquired drug resistance is considered a major obstacle contributing to the failure of sorafenib treatment in HCC patients. 31 , 32 Previous studies have shown that sorafenib treatment restrained tumor growth partly through suppression of tumor angiogenesis. However, sorafenib treatment can lead to the activation of HIF‐1α or HIF‐2α in cancer cells, which in turn induce the expression of VEGF and other proangiogenic factors to confer HCC resistance to sorafenib treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation of hepatocellular carcinoma cells has indicated that drug resistance negatively associates with reduced levels of miR-20b [ 80 ]. Overexpression of miR-20b leads to the sensitivity of hepatocellular cancer cells to chemotherapy drugs.…”
Section: Approaches To Determine the Targets Of Mir-20bmentioning
confidence: 99%
“…Overexpression of miR-20b leads to the sensitivity of hepatocellular cancer cells to chemotherapy drugs. From the molecular aspect, the cell division cycle 37-like 1 (CDC37L1) gene enhances drug resistance of hepatocellular cancer cells [ 80 ]. Targeting CDC37L1 by miR-20b reverses its effects.…”
Section: Approaches To Determine the Targets Of Mir-20bmentioning
confidence: 99%